PERSEBARAN AIR LINDI TPA BENOWO TERHADAP KUALITAS AIR TAMBAK - Munawar Ali; Annisa Nurjanna (EnviroUS, 2021)
The Benowo Landfill (TPA) in Surabaya applies the Open Dumping method so that it has the potential to produce leachate which can pollute the surrounding environment. The leachate storage system in TPA Benowo also plays a role in the possibility of leachate leaking into groundwater and polluting the quality of freshwater aquaculture pond water around Benowo TPA. The method used is the purposive sampling method, which is by taking several samples scattered around the center of the Benowo landfill waste dump, then testing the COD concentration, which is then the results of the COD measurement, plotted on a map to analyze the distribution pattern. The results showed that there was an indication that pond water around the Benowo landfill had been contaminated with leachate which was shown by the COD concentration in 14 test samples, only 3 according to the quality standard of PP RI No.82 of 2001.